PENERAPAN PERATURAN MAHKAMAH AGUNG ( PERMA ) NOMOR 2 TAHUN 2012 TENTANG BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KITAB UNDANG-UNDANG HUKUM PIDANA PADA KASUS PENIPUAN DAN PENGGELAPAN DI PENGADILAN NEGERI PEKANBARU - Frestu C Simanjuntak; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Over time, fraud and embezzlement have become the most common crime. Minor fraud and light embezzlement with a value of less than Rp. 2,500,000.00 which was tried in court was enough to attract the attention of the public. The general public considers that it is very unfair if the cases are threatened with a sentence of 4 (four years) imprisonment as regulated in articles 378 and 372 of the Criminal Code because it is not proportional to the monetary value of the crimes committed. Then the Republic of Indonesia Supreme Court Regulation No. 2 of 2012 was issued concerning the Adjustment of Limits of Minor Crimes and the Number of Fines in the Criminal Code. The purpose of this thesis is: First, to find out the Implementation of Supreme Court Regulation Number 2 of 2012 in the Pekanbaru District Court. Second, to find out the legal consequences of the Judges' decision if they do not apply Supreme Court Regulation Number 2 of 2012.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the locations or places studied in order to give a complete and clear picture of the issues examined. This research was conducted at the Pekanbaru District Court, whereas the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data and data tertiary, technical data collectors in this study with interviews and literature study. From the results of the research and discussion it can be concluded that, First, the application of the Supreme Court Regulation No. 2 of 2012 in the Fraud and Embezzlement Cases in the Pekanbaru District Court has not been going well and optimally, this can be seen from the results of research conducted by the author, namely the Judges' Court The State of Pekanbaru in handling minor criminal cases still often does not apply PERMA Number 2 of 2012. Second, the consequences for Judges if they do not apply PERMA Number 2 of 2012 can be subject to sanctions by the Supreme Court, because if judges do not apply PERMA Number 2 of 2012 in adjudicate a misdemeanor then it violates the Code of Ethics and / or the Code of Conduct of judge point C about behaving fairly in section 8.Keywords: Implementationv – Supreme Court Rules – Fraud - Embezzlement